Higher coagulation activity in hip fracture patients: A case‐control study using rotational thromboelastometry. (24th November 2020) - Tsantes, Andreas G.; Trikoupis, Ioannis G.; Papadopoulos, Dimitrios V.; Tsante, Konstantina A.; Mavrogenis, Andreas F.; Koulouvaris, Panagiotis; Savvidou, Olga D.; Kontogeorgakos, Vasilios A.; Piovani, Daniele; Kriebardis, Anastasios G.; Bonovas, Stefanos; Papagelopoulos, Panayiotis J.; et al.
Abstract: Introduction: Trauma‐induced coagulopathy has been extensively investigated in the multitrauma setting, but only sparsely following moderate orthopedic trauma. The purpose of this study was to evaluate changes in the hemostatic profile of patients with hip fractures, using rotational thromboelastometry (ROTEM). Methods: 198 patients with hip fractures who underwent surgery were included in the study. A matched group of 52 healthy individuals was also enrolled. Demographics, conventional laboratory assays, and ROTEM parameters were recorded and compared between patients and healthy adults. The preoperative and postoperative ROTEM values of fractured patients were also compared. Results: The conventional coagulation assays were similar for the 2 groups. However, several ROTEM parameters including EXTEM MCF ( P  < .001), EXTEM alpha angle ( P  < .001), INTEM MCF ( P  < .001), INTEM A10 ( P  < .001), and INTEM alpha angle ( P  < .001) significantly differed between the 2 groups indicating a higher coagulation potential following hip fractures. Also, fractured patients had significantly lower INTEM and EXTEM CT values ( P  = .008 and P  = .012, respectively) and significantly lower INTEM and EXTEM CFT values ( P  < .001). Adjusted analysis for confounders further confirmed the direct relationship between hip fracture and higher coagulation activity. Last, INTEM CT and CFT significantly decreased ( P  = .008 and P  < .001, respectively), while INTEM MCF, A10, and alpha angle significantly increased ( P  < .001) postoperatively, indicating that surgery further increases the coagulation potential. Conclusion: A higher coagulation activity following hip fractures and surgical treatment can be detected by ROTEM shortly after the injury, even when this is undetectable by conventional coagulation assays.